Green Synthesis of Metal and Metal Oxide Nanoparticles and Their Effect on the Unicellular Alga Chlamydomonas reinhardtii - Nguyen, Nhung H A; Padil, Vinod Vellora Thekkae; Slaveykova, Vera I; Černík, Miroslav; Ševců, Alena (Nanoscale research letters, 2018)
Recently, the green synthesis of metal nanoparticles has attracted wide attention due to its feasibility and very low environmental impact. This approach was applied in this study to synthesise nanoscale gold (Au), platinum (Pt), palladium (Pd), silver (Ag) and copper oxide (CuO) materials in simple aqueous media using the natural polymer gum karaya as a reducing and stabilising agent. The nanoparticles' (NPs) zeta-potential, stability and size were characterised by Zetasizer Nano, UV-Vis spectroscopy and by electron microscopy. Moreover, the biological effect of the NPs (concentration range 1.0-20.0 mg/L) on a unicellular green alga (Chlamydomonas reinhardtii) was investigated by assessing algal growth, membrane integrity, oxidative stress, chlorophyll (Chl) fluorescence and photosystem II photosynthetic efficiency. The resulting NPs had a mean size of 42 (Au), 12 (Pt), 1.5 (Pd), 5 (Ag) and 180 (CuO) nm and showed high stability over 6 months. At concentrations of 5 mg/L, Au and Pt NPs only slightly reduced algal growth, while Pd, Ag and CuO NPs completely inhibited growth. Ag, Pd and CuO NPs showed strong biocidal properties and can be used for algae prevention in swimming pools (CuO) or in other antimicrobial applications (Pd, Ag), whereas Au and Pt lack these properties and can be ranked as harmless to green alga.
Keywords: Chlamydomonas reinhardtii; Green chemistry; Metal nanoparticles; Biological effect